<span><span>−6</span>=<span>14−<span>z3</span></span></span> Step 1: Simplify both sides of the equation.<span><span>−6</span>=<span>14−<span>z3</span></span></span>
<span>
<span>Simplify: </span>
</span>
<span><span><span>−6</span>=<span><span><span><span>−1</span>3</span>z</span>+14</span></span> Step 2: Flip the equation.<span><span><span><span><span>−1</span>3</span>z</span>+14</span>=<span>−6</span></span> Step 3: Subtract 14 from both sides.<span><span><span><span><span><span>−1</span>3</span>z</span>+14</span>−14</span>=<span><span>−6</span>−14</span></span><span><span><span><span>−1</span>3</span>z</span>=<span>−20</span></span> Step 4: Multiply both sides by 3/(-1).<span><span><span>(<span>3<span>−1</span></span>)</span>*<span>(<span><span><span>−1</span>3</span>z</span>)</span></span>=<span><span>(<span>3<span>−1</span></span>)</span>*<span>(<span>−20</span>)</span></span></span><span>z=60</span><u> Answer:</u><span><span>z=60</span></span></span>